2018
DOI: 10.1016/j.redox.2018.07.019
|View full text |Cite
|
Sign up to set email alerts
|

The effect of reactive oxygen and nitrogen species on the structure of cytoglobin: A potential tumor suppressor

Abstract: Many current anti-cancer therapies rely on increasing the intracellular reactive oxygen and nitrogen species (RONS) contents with the aim to induce irreparable damage, which subsequently results in tumor cell death. A novel tool in cancer therapy is the use of cold atmospheric plasma (CAP), which has been found to be very effective in the treatment of many different cancer cell types in vitro as well as in vivo, mainly through the vast generation of RONS. One of the key determinants of the cell's fate will be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 73 publications
1
39
0
Order By: Relevance
“…Systemic exposure to insults, such as toxins or bacterial infection, triggers an inflammatory response associated with the release of inflammatory mediators, such as free radicals, cytokines, and chemokines (Milatovic et al, 2017). As a NO scavenger, Cygb has been reported as an anti-inflammatory and antitumor agent (De Backer et al, 2018;Yassin et al, 2018). Ou et al (2018) showed that Cygb prevents atherosclerosis by functioning as an NO dioxygenase enzyme and ROS scavenger, favoring the protection of the body against unbalanced homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic exposure to insults, such as toxins or bacterial infection, triggers an inflammatory response associated with the release of inflammatory mediators, such as free radicals, cytokines, and chemokines (Milatovic et al, 2017). As a NO scavenger, Cygb has been reported as an anti-inflammatory and antitumor agent (De Backer et al, 2018;Yassin et al, 2018). Ou et al (2018) showed that Cygb prevents atherosclerosis by functioning as an NO dioxygenase enzyme and ROS scavenger, favoring the protection of the body against unbalanced homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the anti‐tumor mechanisms are complex and not clear. Cygb performs the activities of peroxidase and nitric oxide dioxygenase (NOD) at O2‐dependent manner . In this study, we observed that Cygb consumes intracellular ROS/RNS and NO storage (Figures A and C), whereas Cygb knockdown aggravates intracellular ROS/RNS and NO accumulation (Figures B and D).…”
Section: Discussionmentioning
confidence: 53%
“…Cygb performs the activities of peroxidase and nitric oxide dioxygenase (NOD) at O2-dependent manner. 12,14,33,34 In this study, we observed that Cygb consumes Thus we proposed that Cygb-mediated ONS control may be a crucial mechanism that determines the function of six-coordinated hemoglobin as tumor suppressors against HCC tumorigenesis and progression.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations